Performance analysis of solar ethanol distillation - N. Vorayos (2018)
Continuous solar ethanol distillation systems having flat-plate and evacuated heat pipe solar collectors are constructed to study their performances and economic viability. The mathematical model of each main component is carried out and the system simulation is developed. The simulated outputs express a reasonable agreement with the experimental results within 14% accuracy. From the simulation, start up with 10% alcohol concentration, the production cost of 80% alcohol concentration from the distillation system of which the yield at 12,500 l/year is evaluated. With the economic analysis, the results show that the use of solar distillation systems appear to be economical compared to the conventional distillation system using fuel oil as heat source. The minimum production cost of the system is 0.39 US$/l. © 2006 Elsevier Ltd. All rights reserved.